Ethical Issues and Decision Making in Collaborative Financial Therapy - D. Bruce Ross; Jerry Gale; Joseph Goetz (Journal of Financial Therapy, 2016)
The purpose of this article is to introduce potential ethical challenges that may arise when a financial and mental health professional collaborate to provide financial therapy and recommendations on how to effectively address these concerns. The development of ethical and professional practices requires extensive dialogue from practitioners in the emerging field of financial therapy; however, it is important to first develop an awareness and sensitivity to the ethical and professional issues across disciplines. This article examines the differences and similarities between the codes of ethics of different financial and mental health disciplines, and addresses six core ethical and professional issues: dual relationships, confidentiality, collaborating with other professionals, fee management, use of technology, and attending to federal and state regulatory laws. In working through the complexity of different disciplines’ regulatory environments, a discussion of how to address these ethical questions in order to progress the financial therapy field is presented.
Keywords: best practices; family therapy; financial planning; financial therapy; ethics; professional collaboration; professional standards